SISTEM APLIKASI MONITORING DAN UPDATE PENGERJAAN PASANG BARU BERBASIS WEB DI PT TELKOM AKSES JAMBI: Monitoring System, Data Processing, Website, PHP - Limia Budiarti, Rike; Puad, Lailyn; Miladinaqwa, Alfin (LP2M Universitas Nurdin Hamzah, 2023)
Within the scope of the company, the system is something that is needed and implemented in it so that the company's operational activities can run well. Monitoring of the running of the system is also necessary so that every job goes according to the rules, which will affect employee performance and as evaluation material for the company to develop an even better system. As in the work on new installations at PT Telkom Access Jambi, it is often found that technicians are slow in updating their work processes in the field and sector heads are also slow in updating order status in their recaps, so this affects the number of installations (active services). less. To minimize these constraints, we need a system that can monitor and update orders so that the processing process is clear, easy and transparent.